Leadership That Inspires: Unlocking Teacher Potential In Islamic Primary Education - Ripai, Ahmad; Santoso, Sigit; Safitri, Hamanda Tantri (IAIN Syekh Nurjati Cirebon, 2025)
This research aims to understand the leadership strategy of madrasah heads in improving teacher performance at Madrasah Ibtidaiyah (MI) Salafiyah Cirebon City. Using qualitative research methods, data was collected through in-depth interviews, observations, and documentation. The results of the study show that madrasah heads have successfully implemented effective strategies such as weekly briefings, the provision of supporting facilities, and strengthening the capacity of teachers through professional development programs to create a conducive work environment and strengthen the relationship between teachers and leaders, as well as arouse teachers' work motivation to continue to develop. However, there are several challenges faced, including limited supervision, technological readiness, and time management. These findings affirm the importance of participatory and communicative strategic leadership and the need for continuous training to maintain and improve the quality of performance in the madrasah environment.Keywords : Strategy, Performance